Adverse effects of a modified regime of intravenous desferrioxamine - Senanayake, M.P.; Silva, W.D.J de; Lamabadusuriya, S.P. (My University, 2001)
The aim of this study was to investigate the side effects to intravenous desferrioxamine in a cohort of thalassaemic patients receiving 100 mg/kg/day of desferrioxamine on 3 consecutive days coinciding with blood transfusions on a long term basis. The patients studied were aged 7-22 yrs and the duration of desferrioxamine therapy exceeded one year. Hypersensitivity in the form of urticaria occurred in one patient and was controlled with prednisolone. None of the patients complained of visual or auditory symptoms. The non thalassaemic control population were not on desferrioxamine, and did not have similar ocular or auditory changes. Six of the study population (mean age 9.3 years) had lens opacities. Abnormal audiograms were present in eight (mean age 10 yrs). The mean ages and the duration of the desferrioxamine therapy of patients with abnormalities was higher than the patients in whom no abnormalities were found. We conclude that the risk of ocular and auditory toxicity increased with duration of desferrioxamine therapy. We recommend monitoring for visual and audiometric changes despite the absence of symptoms even in patients receiving less than the total recommended dose of intravenous desferrioxamine